Modeling of Seismic Progressive Collapse Distribution in 3 Story Symmetric and Asymmetric Reinforced Concrete Buildings - somayyeh karimiyan; aboreza sarvghad moghadam (مجله مدل سازی در مهندسی, 2014)
This paper models the 3D progressive collapse of a 3 story reinforced concrete symmetric/asymmetric building with different levels of mass eccentricity under earthquake loads. We investigate collapse propagation, from the first element to the entire of the buildings, through comparing the results obtained via evaluation of the nonlinear time history analyses. Our analyses signify that mass irregular distributions result in further local damages and consequently are led to a larger progressive collapse in torsional buildings. We found that collapse is tend to be concentrated in the positions with a high level of mass concentration and the collapse distributions are horizontal through the stories, but not vertical through the height of the building. When the value of mass eccentricity is increased, collapse initiation points tend to transfer to the flexible edges and the probability that the collapse is initiated from the columns is increased, too. Besides, the spread of the collapse is independent of the earthquake records and vary according to the level of mass eccentricity in structures. This gives the ability to predict collapse scenarios in similar symmetric/asymmetric buildings.